ARCHETYPE ANALYSIS OF THE MAIN CHARACTERS IN O. HENRY’S SHORT STORY THE GIFT OF THE MAGI (1905) - Mawar Dewanti Wandansari; Yulistiyanti Yulistiyanti (Dinamika Bahasa dan Budaya, 2020)
This study is descriptive qualitative study, the focus of discussion is the archetypes of the characters in the short story “The Gift of the Magi” by O. Henry 1905. This short story represents a love story of a married couple who life in the low economic condition. The main characters are Jim as the husband and Della as the wife. It focuses on the explanation on the characters they have. There are some types of psichologycal study by Carl Jung (1953) that can be used to analyze, but the researcher only choose archetypes with three kinds: Ego, Soul, and Self. The researcher found the characteristics and the types archetypes they have. The most archetypes found is the Lover, it might happens because they are couple and the story tells about their struggle in doing the life together after married. This is also make the reader realize that love does not only come from something luxury, but also from suffering together. The result in this study is archetypes can be found in everytone. This sudy might give and improve the knowledge about artcehtypes for the researcher and readers.